VLA imaging of the XMM-LSS/VIDEO deep field at 1–2 GHz. Issue 3 (20th June 2020) - Heywood, I; Hale, C L; Jarvis, M J; Makhathini, S; Peters, J A; Sebokolodi, M L L; Smirnov, O M
ABSTRACT: Modern radio telescopes are routinely reaching depths where normal star-forming galaxies are the dominant observed population. Realizing the potential of radio as a tracer of star formation and black hole activity over cosmic time involves achieving such depths over representative volumes, with radio forming part of a larger multiwavelength campaign. In pursuit of this, we used the Karl G. Jansky Very Large Array (VLA) to image ∼5 deg 2 of the VIDEO/XMM-LSS extragalactic deep field at 1–2 GHz. We achieve a median depth of 16 µJy beam −1 with an angular resolution of 4.5 arcsec. Comparisons with existing radio observations of XMM-LSS showcase the improved survey speed of the upgraded VLA: we cover 2.5 times the area and increase the depth by ∼20 per cent in 40 per cent of the time. Direction-dependent calibration and wide-field imaging were required to suppress the error patterns from off-axis sources of even modest brightness. We derive a catalogue containing 5762 sources from the final mosaic. Sub-band imaging provides in-band spectral indices for 3458 (60 per cent) sources, with the average spectrum becoming flatter than the canonical synchrotron slope below 1 mJy. Positional and flux density accuracy of the observations, and the differential source counts are in excellent agreement with those of existing measurements. A public release of the images and catalogue accompanies this article.